Application of Ex Vivo Cryo-imaging Technique for Three-Dimensional Finite Element Analysis of Atherosclerotic Plaque Rupture - Abdul-Aziz, Ahmad A; Cotton, Ross; Richards, Simon; Faramarzalian, Ali; Young, Philippe G; Chamie, Daniel; Wilson, David L.; Bezerra, Hiram G.; Costa, Marco A. (British Journal of Healthcare and Medical Research, 2015)
Cryo-imaging is an ex vivo vascular imaging modality that acquires serial 2D fluorescence and bright-field images at 20μm increments without sacrifice to tissue morphology. These features make Cryo-imaging an attractive approach for rendering high-resolution 3D volumes that may serve as a basis for finite element analysis (FEA) studies of plaque rupture. This work demonstrates the first use of Cryo-imaging for the imaging of a human coronary vessel and the subsequent rendering of a 3D FE model that clearly delineates critical anatomical features of atherosclerotic plaque. FEA is then performed to assess the plaque rupture conditions that result in a thrombotic episode.